اتجاهات طلبة الجامعة نحو الدراسة باللغة الانجليزية في الجزائر - نريمان فتيتي; نسرين بالتومي (جامعة الوادي - University of Eloued, 2025)
"ملخص الدراسة: هدفت الدراسة الحالية إلى التعرف على اتجاهات طلبة جامعة الوادي نحو الدراسة باللغة الانجليزية في الجزائر، ولتحقيق أهداف الدراسة اتبعنا المنهج الوصفي التحليلي المقارن باعتباره الأنسب لوصف الظاهرة وجمع المعلومات ومتابعتها في الميدان للحصول على بيانات حقيقية، وقد أجريت الدراسة في أربع كليات بجامعة الشهيد حمه لخضر وهي (كلية العلوم الاجتماعية والانسانية / كلية علوم الطبيعة والحياة / كلية العلوم الاقتصادية وعلوم التسيير / كلية التكنولوجيا)، حيث تكونت العينة من 150 طالبا وطالبة، تم اختيارهم بطريقة عشوائية بسيطة، وذلك بعد توزيع الاستبيان عليهم المتكون من 30 بند المصمم من قبل الطالبيتين، ولتصحيح الأداة تم الاعتماد على سلم ليكارت الخماسي، كما تمت الاستعانة بالبرنامج الإحصائي للعلوم الاجتماعية (.(spss وقد توصلت الدراسة إلى النتائج التالية:  وجود اتجاهات إيجابية لدى طلبة جامعة الوادي نحو الدراسة باللغة الانجليزية.  اتجاهات طلبة جامعة الوادي نحو الدراسة باللغة الانجليزية لا تختلف باختلاف الجنس.  عدم وجود فروق ذات دلالة إحصائية في اتجاهات طلبة جامعة الوادي نحو الدراسة باللغة الانجليزية تعزى إلى اختلاف انتمائهم الكلياتي.  وجود علاقة ذات دلالة إحصائية بين اتجاهات طلبة جامعة الوادي نحو الدراسة باللغة الانجليزية ومستوى كفاءتهم اللغوية في اللغة الانجليزية. "Abstract: The current study aimed to identify the attitudes of students at the University of El Oued toward studying in English in Algeria. To achieve the study objectives, we used a descriptive-analytic comparative approach, as it is the most appropriate for describing the phenomenon, collecting information, and monitoring them in the field to obtain real-world data. The study was conducted in four faculties of Martyr Hama Lakhdar University, namely (Faculty of Social and Human Sciences / Faculty of Natural and Life Sciences / Faculty of Economics and Management / Faculty of Technology). The sample consisted of 150 male and female students, selected randomly, after distributing a questionnaire consisting of 30 items designed by the two students. To correct the tool, we relied on a five-point Likert scale and used the Statistical Software for Social Sciences (SPSS). The stud yielded the following results:  There is a positive attitude among El Ouad University students towards studying in English.  El Ouad University students' attitudes towards studying in English do not differ by gender.  There are no statistically significant differences in El Ouad University students' attitudes towards studying in English attributable to differences in their university affiliation.  There is a statistically significant relationship between El Ouad University students' attitudes towards studying in English and their level of English language proficiency.
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص علم نفس المدرسي
Keywords: دراسة اللغة الانجليزية; اتجاهات طلبة جامعة الوادي; الطلبة; الاتجاه; Attitudes; Students; University of El Oued students' attitudes; English language study